The comparative study of Alkanna and Huynhia (Boraginaceae, Lithospermeae), with description of a new species in Iran - Khalvati, Sina; Ranjbar, Massoud (Phytotaxa, 2021)
A new blue to light violet-flowered species from SW Iran is described as Alkanna semiromica. The new species is morphologically close to A. frigida and Huynhia pulchra. Floral characters suggested the affinity of the new species to Huynhia, especially the stamens inserted at different heights in the corolla tube and also the plant trichomes while the pollen characters supported its place within the genus Alkanna. A comparison with the new species and the most similar genera is presented here based on new and old morphological data, to understand the differences among the species. In addition, the diagnostic characters, description, detailed illustrations, and taxonomic comments are presented.